Alterações no perfil tegumentar decorrentes do tratamento da classe II esquelética com o aparelho de protração mandibular - Leal, Leanne Matias Portela (2013)
The present study aimed to evaluate changes in soft tissue profile that result from treating skeletal Class II malocclusions with a mandibular protraction appliance (MPA). To this end, two groups were formed. Group 1 - The experimental group, consisting of 22 subjects, 11 females and 11 males, mean age 12.09 (0.87 months), with skeletal Class II malocclusion and mandibular deficiency treated with an FLFtype MPA at the peak of pubertal growth, and Group 2 The control group, comprising 21 subjects, 10 females and 11 males, mean age 11.83 (0.5 months), with similar malocclusions, no history of orthodontic treatment, and at the peak of pubertal growth. Lateral radiographs were taken prior to placing the MPA and after its removal, 10 months later (1,08), in the experimental group. Two radiographs were also taken of the control group, the first to determine the bone age of the experimental group, and the second 11,1 months thereafter (1,08). Statistical analysis was performed using Student s t-test with 5% significance level. Based on the results, it was found that treatment of skeletal Class II malocclusion with an FLFtype MPA induced changes in soft tissue profile, notably characterized by upper lip retraction and reduced facial convexity. Furthermore, anterior repositioning of the chin was observed which, however, varied widely between individuals, and was not statistically significant